Age- and sex-related difference of lipid profile in patients with ischemic stroke in China. Issue 23 (June 2018) - Zhao, Pingsen; Liu, Sudong; Zhong, Zhixiong; Liu, Jing
Abstract : Abstract: Age- and sex-related differences of lipid profiles were not well understood among ischemic stroke patients in China. Our study aimed to investigate the relationship between lipid abnormalities and ischemic stroke in China. A retrospective analysis was performed involving 2074 patients with ischemic stroke who admitted to Meizhou People's Hospital (Huangtang Hospital), Meizhou Hospital Affiliated to Sun Yat-sen University between January 1, 2014 and March 1, 2017. Our study indicated that there were significant differences in total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), non-high density lipoprotein cholesterol (non-HDL), and Apolipoprotein A (ApoA) between male and female patients. Meanwhile, different lipid levels including TC, TG, and ApoA were observed for patients of various age groups. The nonelderly patients tended to have higher lipid levels than elderly patients. Isolated low HDL (namely, normal LDL + low HDL + normal TG) was the most common lipid abnormalities in patients. In conclusion, there was age- and sex-related difference in lipid profiles among patients with ischemic stroke. Age, sex as well as some other factors should be carefully considered for lipid management in patients with ischemic stroke in China.